Cyclospora Cayetanensis-Major Outbreaks from Ready to Eat Fresh Fruits and Vegetables - Hadjilouka, Agni; Tsaltas, Dimitrios (My University, 2020)
Cyclospora cayetanensis is a coccidian protozoan that causes cyclosporiasis, a severe gastroenteric disease, especially for immunocompromised patients, children, and the elderly. The parasite is considered as an emerging organism and a major contributor of gastroenteritis worldwide. Although the global prevalence of cyclosporiasis morbidity and mortality has not been assessed, global concern has arisen since diarrheal illness and gastroenteritis significantly affect both developing countries and industrialized nations. In the last two decades, an increasing number of foodborne outbreaks has been associated with the consumption of fresh produce that is difficult to clean thoroughly and is consumed without processing. Investigations of these outbreaks have revealed the necessity to increase the awareness in clinicians of this infection, since this protozoan is often ignored by surveillance systems, and to establish control measures to reduce contamination of fresh produce. In this review, the major cyclosporiasis outbreaks linked to the consumption of ready to eat fresh fruits and vegetables are presented.
Keywords: Cyclospora cayetanensis; Major outbreaks; Fresh produce